Rice husk-derived nanosilica alleviates aluminum accumulation and toxicity in Brassica napus by regulating cellular metabolism and antioxidant defense - Raheel Munir; Nazia Jan; Bahar Ali; Rana Muhammad Amir Gulzar; Muhammad Haseeb Javaid; Iqbal Hussain; Yinbo Gan (Environmental Research, 2026)

Optimizing Nitrogen Fertilization through Combined Sources and Split Humic Acid Application Improves Wheat Productivity and Stress Resilience in Semi-arid Soils - Tahir Fazal; Muhammad Aurangzaib; Umar Arshad; Rashid Iqbal; Muhammad Raheel; Allah Ditta; Mohamed Taha Yassin (Water, Air, & Soil Pollution, 2026)

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Evolution and Biogeography of the Genus Heteropoda (Heteropodinae: Sparassidae) Across Southeast Asia - Shakal Khan Korai; Amir Khan Korai; Shengnan Li; Kamil Kabir; Kamran Haider; Muhammad Raheel Tariq; Arif Ali; Xiaoshan Wang (Zoologica Scripta, 2026)
Heteropoda huntsman spiders are large, fast‐moving predators widely distributed across tropical and subtropical regions, where they function as important nocturnal hunters. Despite their ecological prominence, the evolutionary and biogeographic history of the genus remains poorly resolved. Here, we analysed a six‐locus dataset (two mitochondrial and four nuclear genes) to estimate divergence times and reconstruct ancestral ranges within Heteropoda using Bayesian phylogenetic and statistical biogeographic approaches, and we assessed broad climatic suitability using genus‐level ecological niche modelling. Time‐calibrated analyses support the monophyly of Heteropoda and indicate that crown diversification began during the early Oligocene (~30 Ma; 95% HPD: 18–41 Ma). A primary split between Australasian and Asian lineages is inferred near the Oligocene–Miocene transition (~23 Ma; 95% HPD: 14–33 Ma), followed by radiation within Southeast and East Asia. Ancestral‐area reconstructions consistently recover Australasia as a key ancestral component and suggest repeated dispersal and isolation across the Sunda–Wallacea interface under conditions of long‐term tectonic instability. Ecological niche modelling identifies temperature, precipitation, and elevation as major correlates of climatic suitability, consistent with the predominance of Heteropoda in warm and humid environments. Together, these results provide an integrated temporal, spatial, and ecological framework for understanding diversification and present‐day distribution of Heteropoda across Southeast Asia and adjacent regions.

Influence of thermal pretreatment on characteristic and anaerobic digestion of Sunflower meal - Asad Ayub Rajput; Zeshan; Muhammad Raheel Bawani; Saleem Raza Chalgri (Bioresource Technology Reports, 2026)

Correction: Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat‑Ul‑Ain Raza (Environmental Geochemistry and Health, 2026)

Efficacy and safety of lorundrostat in uncontrolled hypertension: A GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Shree Rath; Javeria Javed; Akif Shahid Khan; Abdul Moiz; Muhammad Ansab; Alishba Hameed; Zaryab Bacha; Zarar Ahmad Khan Afridi; Khushal Khan; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Modeling the interplay of cultivars, irrigation regimes, and planting dates for optimizing cotton productivity in core and non-core cotton areas of Pakistan - Raheel Osman; Muhammad Shahid Iqbal; Zareen Sarfraz; Abid Mahmood; Muhammad Rafiq Shahid; Til Feike; Lin Wang; Shenglei Fu; Syed Tahir Ata-Ul-Karim (Computers and Electronics in Agriculture, 2026)

Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza (Environmental Geochemistry and Health, 2026)

Intravenous thrombolysis as an adjunct to endovascular thrombectomy in acute basilar artery occlusion: a GRADE-assessed systematic review and meta-analysis - Shree Rath; Umama Alam; Aamna Kashif; Muhammad Ansab; Hafiza Tooba Siddiqui; Muhammad Burhan; Zarar Ahmad Khan Afridi; Ahmad Khan; Aiman Gulalay; Bilal Aslam; Raheel Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrated water and nitrogen management sustains rice yield and efficiency under changing climate scenarios - Fazli Hameed; Muhammad Mannan Afzal; Anis Ur Rehman Khalil; Junzeng Xu; Shah Fahad Rahim; Raheel Osman; Khalil Ahmad; Yongqiang Li; Tangyuan Ning (Agricultural Systems, 2026)

Spatial assessment and ecological risk evaluation of soil heavy metal contamination using multivariate statistical techniques - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza; Goh Choo Ta; Sharina Binti Abdul Halim (CATENA, 2025)

Identification of a biallelic MMUT variant (p.Thr230Arg) and its global perspective on clinical management - Sumreena Mansoor; Qamar Ali; Sabeen Abid Khan; Munir Iqbal Malik; Muhammad Imran; Raheel Qamar; Maleeha Azam (Molecular Biology Reports, 2025)

Kojic acid suppresses browning incidence, maintains quality and sensory attributes of harvested loquat fruit by upregulating enzymatic and non-enzymatic antioxidants - Saqib Ayyub; Ahmad Sattar Khan; Raheel Anwar; Abdul Rehman; Hafiz Muhammad Shoaib Shah; Sajid Ali (Postharvest Biology and Technology, 2025)

Gum Arabic Organic Coating Maintains Freshness and Modulates Oxidative Stress by Augmenting the Antioxidant Activities of Harvested Ber Fruit - Alisha Noor; Ahmad Sattar Khan; Raheel Anwar; Sajid Ali; Rana Naveed Ur Rehman; Saqib Ayyub; Muhammad Haider Ali (Applied Fruit Science, 2025)

Elucidating the synergistic activity of biocontrol agents in combating Xanthomonas citri pv. malvacearum and promoting of physio-chemical responses in cotton - Usman Arshad; Yaxing Feng; Muhammd Raheel; Waqas Ashraf; Muhammad Amjad Ali; Iqra Naeem; Kexin Liu (Physiological and Molecular Plant Pathology, 2025)

Green-engineered calcium-doped carbon nanospheres enhance salt tolerance and growth in maize by modulating gene expressions and antioxidant defense mechanisms - Muhammad Haseeb Javaid; Bahar Ali; Asifa Neelam; Syed Asad Hussain Bukhari; Raheel Munir; Zulqarnain Haider; Muhammad Rehman; Hafiza Arooj Razzaq; Abdul Majeed; Yinbo Gan (Journal of Environmental Chemical Engineering, 2025)

Harvest Time Influences Quality and Storability of ‘Chandler’ Strawberries Grown Under Subtropical Conditions of Pakistan - Ayesha Maryam; Raheel Anwar; Mahmood Ul Hasan; Sajid Ali; Ahmad Sattar Khan; Muhammad Moaaz Ali; Khurram Ziaf (Applied Fruit Science, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

Manipulation of root-associated bacterial endophytes for sustainable crop production system: A review - Maqsood Ahmed Khaskheli; Mir Muhammad Nizamani; Entaj Tarafder; Diptosh Das; Ghulam Muhae-Ud-Din; Raheel Ahmed Khaskheli; Yong Wang (Rhizosphere, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Unveiling the sweetness: evaluating yield and quality attributes of early generation sweet corn (Zea mays subsp. sachharata) inbred lines through morphological, biochemical and marker-based approaches - Shah Mohammad Usman; Raheel Shafeeq Khan; Asif Bashir Shikari; Nida Yousuf; Showkat Ahmad Waza; Shabir Hussain Wani; Muhammad Ashraf Bhat; F. Shazia; Faroq Ahmad Sheikh; Asma Majid (Molecular Biology Reports, 2024)

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Unlocking plant secrets: A systematic review of 3D imaging in plant phenotyping techniques - Muhammad Salman Akhtar; Zuhair Zafar; Raheel Nawaz; Muhammad Moazam Fraz (Computers and Electronics in Agriculture, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Hierarchical S-scheme heterojunction systems: A comprehensive review on outstanding photocatalysts - Huimin Han; Muhammad Raheel Khan; Irshad Ahmad; Ayman Al-Qattan; Ijaz Ali; Md Rezaul Karim; Hossein Bayahia; Farhat S. Khan; Zubair Ahmad; Saad Ullah (Journal of Water Process Engineering, 2024)

Elucidating the Mechanism of Copper-Induced Photoluminescence Quenching in 2-Phenylbenzimidazole-5-Sulfonic Acid - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Poshmal Sumreen; Mamoona Tabassum; Shoaib Ashiq; Sheikh Aadil Abbas; Raheel Akram; Azhar Iqbal (Journal of Fluorescence, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

Interactive mode of biochar-based silicon and iron nanoparticles mitigated Cd-toxicity in maize - Muhammad Umair Yasin; Fakhir Hannan; Raheel Munir; Sajid Muhammad; Muhammad Iqbal; Iqra Yasin; Muhammad Saad Shoaib Khan; Farah Kanwal; Yang Chunyan; Xingming Fan; Yinbo Gan (Science of The Total Environment, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Differential accumulation pattern of cadmium in plant parts of pea varieties in response to varying cadmium levels - Khurram Ziaf; Hafiz Muhammad Talha; Muhammad Awais Ghani; Iftikhar Ahmad; Raheel Anwar; Basharat Ali; Yasir Majeed; Amir Shakeel; Mudassar Iqbal; Abbu Zaid (South African Journal of Botany, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Staphylococcus Sciuri SAT-17 Facilitated in Vitro Regenerated Sugarcane Plantlets Cultivation in Saline Soil by Harmonizing Oxidative Signaling, Photosynthetic Efficiency and Nutrients Uptake Patterns - Raheel Parvez Abbasi; Muhammad Sohail Akram; Khadija Rafiq; Saadia Basheer; Naeem Iqbal (Journal of Soil Science and Plant Nutrition, 2023)

Characterization of Corn Oil Using Fluorescence Spectroscopy - Saud Abdullah; Muhammad Asif; Hina Ali; Raheel Ali; Muhammad Saleem (Journal of Fluorescence, 2022)

Plant Growth and Fruit Quality Response of Strawberry is Improved After Exogenous Application of 24-Epibrassinolide - Muhammad Moaaz Ali; Raheel Anwar; Aman Ullah Malik; Ahmad Sattar Khan; Saeed Ahmad; Zahoor Hussain; Mahmood Ul Hasan; Mudassar Nasir; Faxing Chen (Journal of Plant Growth Regulation, 2022)

Sonolytic-ozonation technology for sanitizing microbial contaminants and pesticide residues from spinach (Spinacia oleracea L.) leaves, at household level - Zarghona Siddique; Aman Ullah Malik; Muhammad Rafique Asi; Raheel Anwar; Muhammad Inam Ur Raheem (Environmental Science and Pollution Research, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Elevated anxiety, hypoactivity, memory deficits, decreases of brain serotonin and 5-HT-1A receptors expression in rats treated with omeprazole - Sadia Basharat Ali; Khalid Mahmood; Raheel Saeed; Tabinda Salman; Muhammad Iqbal Choudhary; Darakhshan Jabeen Haleem (Toxicological Research, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

Decoupled Hydrodynamic Models and Their Outdoor Identification for an Unmanned Inland Cargo Vessel with Embedded Fully Rotatable Thrusters - Gerben Peeters; Senne Van Baelen; Gökay Yayla; Tim Catoor; Muhammad Raheel Afzal; Christos Christofakis; Robrecht Louw; Yogang Singh; Maarten Vanierschot; René Boonen; Peter Slaets (Journal of Marine Science and Engineering, 2020)
Expanding the automation level of the freshly introduced fleet of self-propelled Watertruck+ barges, which house fully-rotatable embedded thrusters, might increase their ability to compete with their less sustainable but dominating road-based alternatives. Hydrodynamic motion models, which reveal the manoeuvring capabilities of these barges, can serve as inputs for many pieces of this automation puzzle. No identified motion models or hydrodynamic data seem to be publicly available for the hull design and the novel actuation system configuration of these barges. Therefore, this study offers: (i) decoupled motion model structures for these barges for surge, sway, and yaw, with a focus on the thruster and damping models; (ii) two identification procedures to determine these motion models; (iii) all the experimental data, generated outdoors with a scale model barge to identify (i) based on (ii). In addition, the identified surge models were compared with both computational and empirical data. These comparisons offer more physical insights into the identified model structures and can aid in the model selection for which the desired complexity and accuracy evidently depend on their envisaged application. Finally, this methodology need not be limited to the vessel and actuation types utilised by us.

An Inland Shore Control Centre for Monitoring or Controlling Unmanned Inland Cargo Vessels - Gerben Peeters; Gökay Yayla; Tim Catoor; Senne Van Baelen; Muhammad Raheel Afzal; Christos Christofakis; Stijn Storms; René Boonen; Peter Slaets (Journal of Marine Science and Engineering, 2020)
Augmenting the automation level of the inland waterway cargo transport sector, coupled with mechatronic innovation in this sector, could increase its competitiveness. This increase might potentially induce a sustainable paradigm shift in the road-dominated inland cargo transport sector. A key enabler of this envisaged shift may be an inland shore control centre (I-SCC) capable of remotely monitoring and controlling inland vessels. Accordingly, this study investigated the concept and design requirements to achieve an inland I-SCC that provides interaction services when supervising an unmanned surface vessel (USV). This I-SCC can help its operator to develop situational awareness and sensemaking. The conducted experiments offered insights into the performance of both the I-SCC system and its operator, and unlock research on the impact on ship sense and harmony when remotely controlling a USV. The Hull-To-Hull project extends the current I-SCC by providing enhanced motion control. This enhancement enables further performance insights and might improve the future monitoring of USVs. The successful I-SCC construction, the preliminary experiments, and the design-extension demonstrate that the I-SCC can serve as an experimental platform for both mechatronic innovation and human-automation integration research in the inland waterway sector, whilst additionally providing fruitful knowledge for adjacent research domains.

Model Structures and Identification for Fully Embedded Thrusters: 360-Degrees-Steerable Steering-Grid and Four-Channel Thrusters - Gerben Peeters; Muhammad Raheel Afzal; Maarten Vanierschot; René Boonen; Peter Slaets (Journal of Marine Science and Engineering, 2020)
The European Watertruck + project introduced a new fleet of self-propelled inland cargo barges to the European waters, in order to induce more sustainable freight transport in the European hinterland. An augmentation of the automation level of this fleet could further advance their competitiveness and potentially pave the way for unmanned inland cargo vessels. The motion control of such a vessel forms a key component in this envisaged automation chain and benefits from the knowledge of the capabilities of the propulsion system, which here envelops a 360-degrees-steerable steering-grid thruster in conjunction with a 360-degrees-steerable four-channel thruster. Therefore, this study details the mechanical design of both thrusters and lists their experimental towing-tank data. Furthermore, two different modelling methods are offered, one theoretically based and one using a multilayer neural network. A model structure comparison, based on a bias-variance trade-off, verifies the adequacy of the theoretical model which got expended with an angle-dependent thrust deduction coefficient. In addition, several multilayer feedforward neural network architectures exemplify their inherent capability to model the complex, nonlinear, flow phenomena inside the thrusters. These identified model structures can additionally improve thrust allocation algorithms and offer better plant models to study more advanced control strategies.

Interactive Effect of Zinc Fertilization and Cultivar on Yield and Nutritional Attributes of Canola (Brassica napus L.) - Abdul Manaf; Muhammad Raheel; Ahmad Sher; Abdul Sattar; Sami Ul-Allah; Abdul Qayyum; Qaisar Hussain (Journal of Soil Science and Plant Nutrition, 2019)

Assessment of resistance to bacterial wilt incited by Ralstonia solanacearum in tomato germplasm - Muhammad Naveed Aslam; Tariq Mukhtar; Muhammad Arshad Hussain; Muhammad Raheel (Journal of Plant Diseases and Protection, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Variants in the PRPF8 Gene are Associated with Glaucoma - Shazia Micheal; Barend F. Hogewind; Muhammad Imran Khan; Sorath Noorani Siddiqui; Saemah Nuzhat Zafar; Farah Akhtar; Raheel Qamar; Carel B. Hoyng; Anneke I. den Hollander (Molecular Neurobiology, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Landslide dam and subsequent dam-break flood estimation using HEC-RAS model in Northern Pakistan - Mohsin Jamil Butt; Muhammad Umar; Raheel Qamar (Natural Hazards, 2013)

Novel and recurrent LDLR gene mutations in Pakistani hypercholesterolemia patients - Waqas Ahmed; Muhammad Ajmal; Ahmed Sadeque; Roslyn A. Whittall; Sobia Rafiq; Wendy Putt; Athar Khawaja; Fauzia Imtiaz; Nuzhat Ahmed; Maleeha Azam; Steve E. Humphries; Raheel Qamar (Molecular Biology Reports, 2012)

A molecular evaluation of dengue virus pathogenesis and its latest vaccine strategies - Muhammad Faheem; Ummar Raheel; Muhammad Nasir Riaz; Naghmana Kanwal; Farakh Javed; Najam us Sahar Sadaf Zaidi; Ishtiaq Qadri (Molecular Biology Reports, 2011)

Role of tissue plasminogen activator and plasminogen activator inhibitor polymorphism in myocardial infarction - Waqas Ahmed; Meera Malik; Imran Saeed; Amina Ali Khan; Ahmed Sadeque; Umar Kaleem; Nuzhat Ahmed; Muhammad Ajmal; Maleeha Azam; Raheel Qamar (Molecular Biology Reports, 2011)

Identification of a recurrent insertion mutation in the LDLR gene in a Pakistani family with autosomal dominant hypercholesterolemia - Muhammad Ajmal; Waqas Ahmed; Ahmed Sadeque; Syeda Hafiza Benish Ali; Syed Habib Bokhari; Nuzhat Ahmed; Raheel Qamar (Molecular Biology Reports, 2010)